Hepato-defensive effect of Cysteine, Ursodeoxycholic acid and Silymarin on histopathological and some biochemical parameters of Wister albino rat intoxicated by CCl4 - Treefa Farouq Ismail; Muhammed Saed, Hero; Zeyan Abdullah Ali; Sarwar Nawzad Jafar (Zanco Journal of Pure and Applied Sciences, 2022)
The liver is an essential organ in the body for detoxification drugs and toxic substances. The present study was designed to investigate the hepatoprotective effects of L-Cysteine, Ursodeoxycholic acid (Ursoflor), and Silymarin against carbon tetrachloride-induced liver injury in rats. Twenty adult male rats were used in this work; they were randomly divided into five groups (4 rats/group). The first group served as the control group and received 0.5 ml of normal saline orally daily; the second group injected intraperitoneally with CCl4 (1.5 ml/kg B.W. twice a week), the third group were treated orally with the silymarin at dose of (200 mg/kg B.W. in normal saline orally + CCl4 daily, the fourth group was treated with Ursoflor drug at dose of (50 mg/kg B.W. in 0.5 normal saline orally+CCl4 daily. While the fifth group was treated with cysteine at dose of (50mg/kg B.W. in normal saline by oral gavage) +CCl4. at the end of this study, the biochemical assessment showed alterations in enzyme activity which indicates the hepatocyte injury due to CCl4 toxicity, The production of ROS indicated by elevated levels in MDA and Peroxynitrite was noticed, which improved partially by the antioxidant effect of L- Cysteine, Ursodeoxycholic acid, and Silymarin, these results further backed by histological examination of the liver showed that CCl4 caused severe injury to the liver including a high number of fat droplets deposition in the cytoplasm of the hepatocyte, clear vascularization appeared and disorganization of the liver cells were determined, on the other hand, Silymarin has showed good protection against these injurious effects of CCl4.